The views of farm animal veterinarians about their roles and responsibilities associated with on-farm end-of-life situations - Deelen, Ellen; Meijboom, Franck L. B.; Tobias, Tijs J.; Koster, Ferry; Hesselink, Jan-Willem; Rodenburg, T. Bas (Frontiers in Animal Science, 2022)
Farm animal veterinarians are often involved in on-farm end-of-life (EoL) decisions and questions concerning euthanasia. These decisions can be challenging for the veterinarian, particularly if the interests of the animal and owner conflict. Moreover, the challenge is related to fundamental assumptions about roles and responsibilities veterinarians ascribe to themselves in EoL situations. Getting insight into what roles and responsibilities veterinarians perceive in these situations is important to understand the challenges veterinarians face and to explore ways to enable them to manage such situations. Existing literature and professional guidelines do not provide sufficient clarity and guidance in terms of the role conception and responsibilities of veterinarians in on-farm EoL situations. The objective of the current qualitative study was to better understand the views of farm animal veterinarians in the Netherlands regarding their roles and responsibilities associated with on-farm EoL situations. In-depth semi-structured interviews were conducted with 19 farm animal veterinarians. In terms of roles in EoL situations, our analysis shows that 1) seven roles can be distinguished based on the interviews, 2) two contextual dimensions influence role perception: a) the stage in which a veterinarian gets involved at the end of an animal’s life and b) the question of whose interests should be taken into consideration and how to prioritize (conflicting) interests by a veterinarian, 3) veterinarians enact a number of the identified roles and the combination of roles varies between individuals and 4) the individual veterinarian changes between roles depending on contextual aspects. In terms of responsibilities in EoL situations, analyses show that 1) individual veterinarians perceive a combination of five identified responsibilities, and 2) the perception of responsibilities relates predominantly to specific animal sectors. This insight into the roles and responsibility perceptions of veterinarians facilitates understanding the challenges veterinarians face in on-farm EoL situations and creates a starting point for how veterinarians can be supported to deal with potential conflicts of interest. These insights could also be valuable in the training of future veterinarians and lifelong learning of veterinarians as it provides a starting point to reflect on, and discuss, one’s role and responsibility in EoL situations.